The Epidemiology of Ankle Sprain During Hiking in Uniformed Groups - Lam Wai-Ho Oscar (Journal of Orthopaedics, Trauma and Rehabilitation, 2011)
Purpose: To determine the prevalence of ankle sprain during hiking training in uniformed groups and identify the risk factors of ankle sprain and the risk factors associated with residual problems after ankle sprain. Methods: A retrospective cross-sectional study involved 590 members of a uniformed group from secondary schools and their leaders by means of a self-administered anonymous questionnaire. Results: The prevalence of ankle sprain was 9.15%. Most of them were lateral sprains (70.4%) and occurred in scree ground (51.9%) and downhill slope (50.0%). Subjects who are “older” aged, are overweight, are leaders in uniformed groups, have a past history of ankle sprain or problem, have a long-term lower limb injury, wear inadequate sized or tight shoes, and use hiking poles, have significant risks. The prevalence of having residual problems after ankle sprains was 48.14%, and the most common one was residual ankle pain (25.0%). Conclusion: Uniformed group leaders and members should be aware of the risk factors of ankle sprain during hiking training in the countryside. They should also be aware of the importance of proper treatment and rehabilitation to prevent residual ankle problem. Level of Evidence: Level II prognostic study.